1985
DOI: 10.1364/josaa.2.000896
|View full text |Cite
|
Sign up to set email alerts
|

Line integrals and physical optics Part II The conversion of the Kirchhoff surface integral to a line integral

Abstract: A new approach is presented for converting the surface integral, representing the Kirchhoff diffracted field of an aperture on a plane screen, to a line integral. It has the advantages that it is mathematically rigorous and explicit and that it results in a representation that has exactly the same properties as the original Kirchhoff formula, i.e., it admits arbitrary source distributions and it is continuous everywhere in the source-free half-space, including the geometric-optics shadow boundary. Moreover, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…The terms used to discretise the surface quantities are therefore defined not only on the surface but also as waves in the medium. If these basis functions satisfy the wave equation then it can be shown (using a transform developed for the problem of aperture diffraction [12,13,14]) that their scattering can be stated as a geometric term plus an edge-diffraction contour integral. Since the contour integrals are 1D it follows that they can be evaluated in ( ) operations, so scale better than standard quadrature methods.…”
Section: 'Wave-matching' Methodsmentioning
confidence: 99%
“…The terms used to discretise the surface quantities are therefore defined not only on the surface but also as waves in the medium. If these basis functions satisfy the wave equation then it can be shown (using a transform developed for the problem of aperture diffraction [12,13,14]) that their scattering can be stated as a geometric term plus an edge-diffraction contour integral. Since the contour integrals are 1D it follows that they can be evaluated in ( ) operations, so scale better than standard quadrature methods.…”
Section: 'Wave-matching' Methodsmentioning
confidence: 99%
“…First it bears a very close resemblance to the energy-inspired time domain BEM algorithms in references 13 and 14, for which unconditional stability can be proven. Secondly it bears a close resemblance to the scattering integral, suggesting that transformation to an edge integral for efficient evaluation may be possible; this has yet to be shown but Asvestas 15 gives a process for converting double integrals of this form into contour integrals. Substituting ‫)ܠ(߮‬ = ‫)ܠ(߰‬ + ‫)ܠ(߯‬ and then breaking down ‫)ܠ(߰‬ into a sum of waves ߰ ܽ,݉ ,݊ f ‫)ܠ(‬ scattered by each basis function yields:…”
Section: Figure 2 Conceptual Separation Of Medium and Obstacle Modelsmentioning
confidence: 99%
“…However, such an indubitable computational advantage is balanced by the presence of singularities in the integrand of the one-dimensional BDW integral, which gives numerical problems, especially whenever the BDW field has to be evaluated close to the geometrical shadow at the observation plane [8]. To overcome such difficulties, important modifications to the BDW theory were provided by several authors [9][10][11][12][13][14][15]. In 2000, Hannay [16] showed that, when the BDW integral (for spherical or plane wave illumination) is written within paraxial approximation, it takes on a mathematical form in which the above singularities are no longer present.…”
Section: Introductionmentioning
confidence: 99%